Risk factors of sudden cardiac death in hypertrophic cardiomyopathy. (January 2022) - Hong, Ying; Su, Wilber W.; Li, Xiaoping
Abstract : Purpose of review: Hypertrophic cardiomyopathy (HCM) is one of the leading causes of sudden cardiac death (SCD) in younger people and athletes. It is crucial to identify the risk factors for SCD in individuals with HCM. This review, based on recent systematic literature studies, will focus on the risk factors for SCD in patients with HCM. Recent findings: An increasing number of studies have further explored the risk factors for SCD in patients with HCM, and new risk markers have emerged accordingly. In addition, more accurate SCD risk estimation and stratification methods have been proposed and continuously improved. Summary: The identification of independent risk factors for HCM-related SCD would likely contribute to risk stratification. However, it is difficult to predict SCD with absolute certainty, as the annual incidence of SCD in adult patients with HCM is approximately 1%. The review discusses the established risk factors, such as a family history of SCD, unexplained syncope and some new risk factors. Taken together, the findings of this review demonstrate that there is a need for further research on individual risk factors and that SCD risk stratification in HCM patients remains a clinical challenge.